Factors that promote and inhibit the entry and permanence of women in Engineering careers at the University of Costa Rica - Vásquez Soto, Carolina (2024)
This article includes the three phases of a gender-perspective research, whose objective was to identify the factors that promote and inhibit the entry and permanence of female students in the area of engineering at the University of Costa Rica. The study was framed in a mixed qualitative-quantitative design. In the first phase, of qualitative methodology, carried out from 2019 to 2020, individual and group interviews were conducted with students. In the second phase, of quantitative methodology, a survey was applied to female students, to identify the incidence of factors in the decision to enroll and remain in the career. Some of the main findings were the importance of skills in Mathematics, Chemistry and Physics in the choice, the UCR ranking and career statistics, as well as the effect of stereotypes in the potential of women in engineering. Regarding permanence, it is concluded that 47% of the women were affected by the macho environment and 21% by situations of sexual harassment. An interesting result was a high valuation of academic efficacy, self-concept and leadership among female students and how this helps them to continue with their studies. This information allowed the elaboration of a proposal to raise awareness among teachers about the factors that inhibit the choice and permanence of female students in in the field of Engineering to be put into practice in the Faculty.